An improved immersed moving boundary for the coupled discrete element lattice Boltzmann method. (30th November 2018) - Cheng, Cheng; Galindo-Torres, S.A.; Zhang, Xiaobing; Zhang, Pei; Scheuermann, A.; Li, Ling
Highlighs: A novel weighting function for the fluid–particle interactions is proposed. The relaxation parameter effect is avoided in the novel weighting function. Parameters a  = 50 and b  = 0.01 are suggested for the proposed weighting function. The smoothing nature of the proposed Bn is necessary for numerical stability. Abstract: In order to improve the accuracy of existing immersed moving boundary method (IMBM) for the coupled discrete element lattice Boltzmann method, a novel weighting function for the fluid–particle interfacial interactions in IMBM is presented in this work. The flow is solved by the three-dimensional lattice Boltzmann method (LBM) D3Q15. The motions of particles are simulated by the discrete element method (DEM). The immersed moving boundary method is applied to resolve the momentum exchange between moving particles and fluids. The solid volume fraction of the fluid cell is calculated by the sphero-polyhedra method. The coupled IMBM–LBM–DEM is programmed based on the open source library Mechsys. The proposed method is validated by simulating flow past a stationary sphere, settling of a sphere and rebound of a spherical particle. These validations demonstrate the accuracy and reliability of this proposed method, which also has a good improvement over the original IMBM. Finally, effects of different parameters in the proposed weighting function are discussed and the suggested values a  = 50, b  = 0.01 are determined. This paper has implications for improving the ability to capture the fluid–particle interactions for a multiphase flow system.